REPRESENTASI NILAI-NILAI KEISLAMAN PADA MAKANAN YANG DISAJIKAN DALAM PERINGATAN TAHUN BARU ISLAM - munasib, Munasib; Rifki Ahda Sumantri; Noor Asyik (Jurnal Tawadhu, 2026)
The discourse on food will always be interesting and evolving, because it is a very basic need and cannot be separated from human survival. In addition to having a vital role and function for human survival, food is believed to have a philosophy behind the food's name. Therefore, this study aims to analyze the semiotics of the naming symbols of food served at the Islamic New Year celebration. The approach used in this research is a multidisciplinary qualitative-interpretive approach, namely by integrating the approach of Islamic religious studies with semiology. The method used in this study is the semiotic analysis method on the naming symbols of food served at the Islamic New Year celebration. This study successfully interpreted the naming symbols of the suro porridge served at the Islamic New Year with reference to its symbolic meaning.